An Assessment on the Locational Pattern of Petrol Filling Stations along Lasu-Isheri Road Corridor - Akinsulire, Esther O.; Fadare, Samson O. (American International Journal of Multidisciplinary Scientific Research, 2020)
This study aimed at assessing the location and spatial distribution of petrol filling stations along LASU/Isheri Road, Ojo, Lagos state. The objectives are to map out all the petrol filling stations in along Lasu/Isheri road; to examine the volume of traffic along the road corridor; to determine the contribution of petrol filling stations to the traffic volume on the road, and to ascertain the road traffic challenges that are caused by the petrol filling stations (PFS). Geographical Positioning System (GPS) was employed to collect primary data; also, questionnaires and traffic count sheets were employed. The study found that the PFS along the road corridor is clustered with a Z-score of -7.34 and NNI of 0.440285. Also, the maximum peak hour volume was estimated to be 4198.6 pcu/hr. The PFS along the corridor are seen to contribute significantly to the traffic volume on the corridor. Finally, the dominant traffic challenges along the corridor include traffic gridlock which sometimes results into road traffic crashes which are triggered by the concentration of PFS in the study area, the proximity of PFS to a road intersection, overflow of the queue into the roadway, and to a minimal extent parking of tankers along the roadway and lack of setback. This study suggests strategies that can be adopted for locating PFS to ensure the free flow of traffic along the road corridor where they are located.